Pengaruh Digital Wellbeing, Cognitive Load, dan Digital Learning Readiness terhadap Hasil Belajar Spreadsheet - M. Azzahra; E. Takidah; S. Susanti (Qalam : Jurnal Ilmu Kependidikan, 2025)
This study examines the partial and simultaneous effects of Digital Wellbeing, Cognitive Load, and Digital Learning Readiness on Spreadsheet Learning Outcomes. A quantitative approach with a survey method and causal associative design was employed. The sample consisted of 125 Grade X Accounting and Financial Institution students from SMKN 40, 48, and 50 in East Jakarta, selected through Proportionate Stratified Random Sampling. Data were collected via a Likert-scale questionnaire and report-card documentation, then analyzed using multiple linear regression. Results show that Digital Wellbeing and Digital Learning Readiness have significant positive effects, while Cognitive Load has a significant negative effect on Learning Outcomes. Collectively, the three variables account for 62.3% of the variance in Learning Outcomes. These findings suggest managing digital device usage duration, structuring clearer teacher instruction, and developing a healthy digital learning ecosystem at school.